Analysis of Regional Financial Capability in the Context of Regional Autonomy in Makassar City - Ina Yulianadewi; Andrew Ridow Johanis; Nurdiana (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
The purpose of this study was to determine and analyze the financial capacity of the region and the contribution of regional original revenue (PAD) to the regional revenue and expenditure budget (APBD) in supporting the implementation of regional autonomy in Makassar City. This research uses quantitative and qualitative research methods (mixed). The results showed that the financial capacity of the city of Makassar experienced a positive trend because it was in the more than adequate category by looking at the ratio of regional financial independence, which resulted in a total of 55.44%. The financial capacity of the city of Makassar from 2014 to 2016 experienced a positive tendency to increase with an average level of 16.43%, the effectiveness of PAD is 110.87%, the priority of expenditure allocation is still on routine spending, the growth of the PAD ratio, income and expenditure has fluctuated growth, and the remainder of the previous year’s budget calculation (SILPA) is decreasing every year. This indicates that the capacity and financial performance of the city of Makassar is quite optimal, so it is necessary to tighten the existing regulations.